Reference Intervals of Factor H and Factor H-Related Proteins in Healthy Children - van Beek, Anna E.; Kamp, Angela; Kruithof, Simone; Nieuwenhuys, Ed J.; Wouters, Diana; Jongerius, Ilse; Rispens, Theo; Kuijpers, Taco W.; Gelderman, Kyra A. (Frontiers in Immunology, 2018)
Complement is activated as part of the innate immune defense against invading pathogens. Also, it helps to remove apoptotic debris and immune complexes from the circulation. Impaired complement function due to aberrant plasma levels of complement proteins may be indicative for complement-mediated diseases, or can be involved in susceptibility for infections. To determine whether plasma levels are abnormal, reference intervals (RIs) are used from adult healthy donors. Since many complement-mediated diseases have an onset during childhood, it is important to know whether these RIs can be extrapolated to children. Reference intervals of Factor H (FH), the crucial fluid-phase regulator, and the FH-related proteins (FHRs), its homologous counterparts, are unknown in healthy children. While FH is measured to diagnose and monitor therapy of patients with atypical hemolytic uremic syndrome, recent studies also implicated increased plasma levels of FHRs in disease. Here, we investigated the levels of FH and FHRs in healthy children using recently developed specific ELISAs. We found that levels of FH, FHR-2 and FHR-3 were equal to those found in healthy adults. Levels of FHR-4A and FHR-5 were lower in children than in adults. However, only the FHR-5 levels associated with age. The RIs of these FH family proteins now serve to support the interpretation of plasma levels in prospective and retrospective studies that can be used for routine diagnostic and monitoring purposes including pediatric patient samples.